Correlation of waist circumference with metabolic syndrome in females attending gynaecology OPD at a tertiary care centre - Mathur, Poonam; Mathur, Pooja; Soni, Shambhavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The metabolic syndrome is an aging-related cluster of metabolic disorders associated with excess adiposity, and plausibly mechanistically linked. The primary goal of recognizing an individual as having the metabolic syndrome was to identify persons at heightened risk for cardiovascular disease (CVD). Secondarily, by design, the diagnosis also helped identify individuals with high risk for other endocrinal imbalance if they did not already have it. So this study was carried out to identify the co-relation between waist circumference and other risk factors with metabolic syndrome and to ascertain their significance. Methods: This is a prospective observational study conducted in Out Patient Department (OPD) of a tertiary care centre with a study population of 50 patients attending OPD with any gynaecological problem having waist circumference > 85 cm. Results: Twenty eight patients (56%) had metabolic syndrome depicting a significant co-relation (p value < 0.05). Thus, increase in WC more than 85cm is directly proportional to the prevalence of metabolic syndrome. Conclusions: We conclude that Waist circumference is directly related to prevalence of metabolic syndrome which is on increase due to sedentary life style. Such patients are also prone to hormonal imbalance, specifically hypothyroidism.